Toeplitz operators on weighted spaces of holomorphic functions - Harutyunyan, Anahit; Lusky, Wolfgang (MATHEMATICA SCANDINAVICA, 2008)
We define a notion of Toeplitz operator on certain spaces of holomorphic functions on the unit disk and on the complex plane which are endowed with a weighted sup-norm. We establish boundedness and compactness conditions, give norm estimates and characterize the essential spectrum of these operators for many symbols.